2018
DOI: 10.1159/000493033
|View full text |Cite
|
Sign up to set email alerts
|

Integrating MicroRNA Expression Profiling Studies to Systematically Evaluate the Diagnostic Value of MicroRNAs in Pancreatic Cancer and Validate Their Prognostic Significance with the Cancer Genome Atlas Data

Abstract: Background/Aims: MicroRNAs (miRNAs) are promising biomarkers for pancreatic cancer (PaCa). However, systemic and unified evaluations of the diagnostic value of miRNAs are lacking. Therefore, we performed a systematic evaluation based on miRNA expression profiling studies. Methods: We obtained miRNA expression profiling studies from Gene Expression Omnibus (GEO) and ArrayExpress (AE) databases and calculated the pooled sensitivity, specificity, and summary area under a receiver operating characteristic (ROC) cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 72 publications
(69 reference statements)
2
18
0
Order By: Relevance
“…The substantial downregulation of miR‐129‐1‐3p in human colon tumors in which c‐Src is activated suggests that miR‐129‐1‐3p is a critical regulator of these cancers. Downregulation of miR‐129‐1‐3p has been observed in some types of cancers, including gastric, hepatocellular, and pancreatic cancer . Previous studies showed that miR‐129‐1‐3p was downregulated by DNA methylation, but the mechanisms downstream of c‐Src that lead to changes in miR‐129‐1‐3p gene expression remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…The substantial downregulation of miR‐129‐1‐3p in human colon tumors in which c‐Src is activated suggests that miR‐129‐1‐3p is a critical regulator of these cancers. Downregulation of miR‐129‐1‐3p has been observed in some types of cancers, including gastric, hepatocellular, and pancreatic cancer . Previous studies showed that miR‐129‐1‐3p was downregulated by DNA methylation, but the mechanisms downstream of c‐Src that lead to changes in miR‐129‐1‐3p gene expression remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Pancreatic ductal adenocarcinoma (PDAC) is the most common pancreatic neoplasm, accounting for approximately 90% of all pancreatic cancers (PCs), with a poor overall survival (OS) rate of 5-8% [1,2]. Over 52% of cases are diagnosed in a distal metastasis stage, with only 3% showing a 5-year OS benefit [3].…”
Section: Introductionmentioning
confidence: 99%
“…In breast cancer and glioma, miR-1301-3p inhibits cell proliferation via downregulating ICT1 and N-RAS, respectively [7,8] . In our previous study, miR-1301-3p was low expressed in PC samples compared with healthy tissues, and a high-level of miR-1301-3p was associated with good OS [9] . Therefore, it is worth investigating the potential functions and mechanisms of miR-1301-3p in PC progression.…”
Section: Introductionmentioning
confidence: 82%